FOREST-BASED LIVELIHOODS AND SOCIAL JUSTICE: AN ANALYSIS OF BENEFIT-SHARING MECHANISMS IN INDONESIA'S SOCIAL FORESTRY SCHEMES - Judijanto, Loso; Amin, Rafiullah; Akhtar, Shazia (Journal of Selvicoltura Asean, 2025)
Social forestry programs are globally promoted as a key strategy, but their equitable outcomes are critical. Indonesia's ambitious social forestry agenda aims to reallocate millions of hectares, prompting this research to critically analyze benefit-sharing mechanisms across key schemes (Hutan Desa, HKm, Hutan Adat). The objective was to evaluate their effectiveness in promoting social justice and community livelihoods. This study employed a qualitative, multi-site case study approach, utilizing 120 interviews and policy analysis through a social justice framework. The findings reveal a significant gap between policy goals and reality: while land tenure improved, benefits often fail to be equitably distributed, being captured by local elites and marginalizing vulnerable groups. Furthermore, procedural justice remains weak due to limited community participation in decision-making. The novelty lies in this critical, justice-focused evaluation of Indonesia's national program. The implication is that for Indonesia's social forestry to succeed, a fundamental redesign of benefit-sharing mechanisms is required. Policy must explicitly embed distributive, procedural, and recognitional justice principles to ensure meaningful livelihood improvements for the poorest and most marginalized community members.